New possibilities for providing services by postal operators through information-communication technology - Kremenova, Iveta; Fabus, Juraj (University of Pardubice, 2018)
In the article, we focused on the business of postal operators in our country and abroad. Based on the results of secondary research about service providing by national postal operators in our country and abroad, we can say that postal services are constantly evolving and modernizing. When comparing the services of the four national postal operators: Slovak Post a.s., Czech Post s.p., Deutsche Post AG and Swiss Post Ltd, we have found that competition in the field is high and therefore every one of them is trying to innovate its services. The Deutsche Post and Swiss Post are mainly focused on information-communication services. The Slovak Post and Czech Post do not use all the opportunities offered by ICT. The article deals not only with the analysis of the services provided by selected postal operators in the Czech Republic and abroad, but also, in particular, with drafts for new services using ICT. This article discusses the use of new ways of delivering shipments.
Keywords: postal operators; technologies; drones; delivery; new services